Serum levels of intestinal alkaline phosphatase in type 2 diabetic patients with enteropathy - Ray, Debkumar; Ray, Mrinal Kanti (International Journal of Research in Medical Sciences, 2019)
Background: Type 2 diabetes mellitus patients frequently have various distressing gastrointestinal signs and symptoms and intestinal alkaline phosphatase (IAP) may be linked to it. Even after extensive search, there was dearth of literature related to IAP levels in serum of diabetic enteropathy subjects. So, using a case-control design, levels of IAP in the serum of T2DM subjects were determined. Methods: Serum IAP was measured by ELISA in 73 type 2 diabetic patients with enteropathy (group 1) and 71 type 2 diabetic patients without enteropathy (group 2). Statistical analysis of the data was performed by using Statistical Package for Social Sciences (SPSS version 16) and inferences were drawn. Results: Serum IAP was highly significantly reduced in group 1 (3.9 U/L) compared to group 2 (4.2 U/L). Conclusions: Enteropathy in T2DM may be related to reduction in IAP levels in serum. Estimation of serum IAP may be considered in type 2 diabetic patients with enteropathy, for the elaboration of treatment strategy and monitoring.